Mechanical relaxation of functionalized carbosilane dendrimer melts. Issue 21 (18th May 2022) - Sheveleva, Nadezhda N.; Dolgushev, Maxim; Lähderanta, Erkki; Markelov, Denis A.
Abstract : Functionalization of the internal structure of dendrimers is a new way to give tailored properties to the dendrimers. Abstract : Functionalizing the internal structure of classical dendrimers is a new way of tailoring their properties. Using atomistic molecular dynamics simulations, we investigate the rheological behavior of functionalized dendrimer (FD) melts obtained by modifying the branching of carbosilane dendrimers (CSD). The time (relaxation modulus G ( t )) and frequency (storage G ′ and loss G ′′ moduli) dependencies of the dynamic modulus are obtained. Fourth generation FD melts present a region where G ′ > G ′′. In contrast, their non-functionalized counterparts ( i.e., classical dendrimers with regular branching) do not show such a region. The comparative analysis of FD and CSD suggests that the internal densification due to functionalization prevents the penetration of branches and causes FD to behave like colloidal particles in a crowded environment. Since CSD have no special interactions, we expect that this effect will be common for other dendrimer macromolecules.